Donald J. Trump’s Protest Response: Rhetorical Language of His Speech at the “Save America” Rally - Adinda Puspa Nur Faiz; Sholikhah, Ika Maratus; Muttaqin, Usep (Elsya : Journal of English Language Studies, 2022)
Language is deliberately utilized by politicians. Admittedly, it can perform a purposive function: to achieve the politicians’ goals crucially in attempt to gain people’s support. This study is interested in the current political context in the U.S. In the 2020 U.S. presidential election, Donald J. Trump lost in his second election. He, therefore, delivers his response of objection at the “Save America” rally in Washington, D.C. This study is targeted to explore a political speech from the defeated candidate perspective. Recently, rhetorical language in political discourse has been commonly analysed. However, this study contributes to an analysis of rhetorical strategy used in an informal, implicit, and pursuing to protest speech by Trump. This study is designed by a descriptive qualitative approach. The data is the speech text of Trump’s speech on 6th January 2021. Technique of data collection undertakes observation of the speech and the transcript, categorization, and coding. The grand theories include Teun van Dijk’s discourse theory (1980) and Reisigl political speech’s schemes (2008). The results indicate that repetition has become Trump’s most potent strategy in his protest speech. Seemingly, he prefers to utilize the devices that are beneficial for him to emphasize something good about Us and emphasize something bad about Them. This is crucial for him since from the defeated side, it can impress the Republicans to support his objection. Nonetheless, Trump’s capability to persuade the Republicans has caused an impulse, anarchic and illegal movement, which is contrary to their ideal vision to the country.